An excited electron avoiding a positive charge - Dutoi, Anthony; Cederbaum, Lorenz S. (The journal of physical chemistry letters, 2011)
High-level ab initio calculations in the time domain reveal the effects of the chemistry in the vicinity of a chomophore unit on the dynamics of an initially localized electronic excitation. An all-electron wavepacket is propagated, and its one-body density matrix is used to divide the dynamic into particle and hole components that can be analyzed separately. The expectation that an excited electron will be attracted to a positively charged ammonium group is superseded by a dynamic in which the hole part of the excitation is driven away from this region, dragging the excited electron with it. These calculations illustrate the crucial role of the attraction between the particle and hole. Emerging time-domain electronic structure techniques hold much promise for unraveling the behavior of complex systems.
Gesehen am 31.03.2022